Beyond the Military State: Sweden’s Great Power Period in Recent Historiography - Thomson, Erik (History compass, 2011)
Sweden’s victories in the Thirty Years War, and the kingdom’s subsequent half-century as a great power, continue to intrigue historians. Historians have argued that Sweden’s success resulted from its rapid construction of a military state, with institutions which efficiently directed a large percentage of its available resources to war. Recent work on the military state has confirmed some of this theory, showing that the kingdom was able to shape institutions, but that this development depended upon bargaining and took a long time. Many strains of recent research, however, suggests that the model of the military state might be reaching the end of its useful life, as it attributes too much agency to Swedish statecraft, and too little to regional influences, internal dissent, cultural forces, and religion.